Men as Women, Women as Men Changing Gender in Native American Cultures - Lang, Sabine (University of Texas Press, 2022)
As contemporary Native and non-Native Americans explore various forms of "gender bending" and gay and lesbian identities, interest has grown in "berdaches," the womanly men and manly women who existed in many Native American tribal cultures. Yet attempts to find current role models in these historical figures sometimes distort and oversimplify the historical realities. This book provides an objective, comprehensive study of Native American women-men and men-women across many tribal cultures and an extended time span. Sabine Lang explores such topics as their religious and secular roles; the relation of the roles of women-men and men-women to the roles of women and men in their respective societies; the ways in which gender-role change was carried out, legitimized, and explained in Native American cultures; the widely differing attitudes toward women-men and men-women in tribal cultures; and the role of these figures in Native mythology. Lang's findings challenge the apparent gender equality of the "berdache" institution, as well as the supposed universality of concepts such as homosexuality